Stare decisis and information abundance in a common law jurisdiction - Emily Roscoe; Charles Szypszak (Review of European and Comparative Law, 2022)
In a common law jurisdiction, according to the principle of stare decisis judges are bound to interpret a constitutional or common law principle by applying authoritative cases already decided. Parties in disputes pending before the courts must find and assess the prior cases on which they can expect that judges will rely. Not very long ago, research for such precedent involved reviewing known cases and linking them to other cases using topical digests and citators. Success with this approach required a patient, persistent, thorough, and open-minded methodology. Modern information accessibility gives previously unimaginable quick access to cases, including with tools that promise to predict judicial tendencies. But this technological accessibility can have negative side effects, including a diminished research aptitude and a stilted capacity to synthesize information. It can also lead to an inadequate account of the human factors that often cause judges to depart from predictions based on logical inference from prior cases. This article considers the extent to which the identification of precedent is essential in legal analysis, yet is of limited value in predictability as a result of judges’ unavoidably human perspectives. With examples from landmark cases, the article illustrates that judges sometimes make decisions based on considerations that will not be revealed in a mechanistic application of precedent. The article considers how evolving legal research tools and methods give access to precedent that in some respects makes the process more scientific, but in other respects can obscure the realities of how cases are decided. The article also gives examples of this paradox as demonstrated by today’s students who are learning how to do research, drawn from years of the authors’ teaching experience.